Tourism, indigeneity, and the importance of place: fighting for heritage at Australia's last frontier - Wergin, Carsten (Lexington Books, 2024)
The book presents a long-term ethnographic study of arguably the largest environmental protest action in Australian history. Carsten Wergin offers a timely discussion of the sociocultural and political relevance of heritage and tourism for ecological preservation and the wider decolonial project in Australia and beyond.
Keywords: Ethik; Feldforschung; Ethnologie; Kulturerbe; Aborigines; Kimberley, Westaustralien